P‐168: Picture Quality and Uniformity Study on High Resolution Top Emission OLED Display Fabricated by Ink Jet Printing Process. Issue 1 (29th May 2019) - Chen, Peng-Yu; Chen, Chien-Chuan; Hsieh, Cheng-Chin; Lin, Yu-Syuan; Li, Chun-Han; Ye, Xuan-Chen; Lu, Hsueh-Hsing; Lin, Kun-Yu
Abstract : To realize a middle size OLED panel (10~20 inch) manufactured by ink jet printing process. A high resolution OLED panel is needed. Because of high resolution, the top emission OLED is requirement to increase the pixel aperture ratio, lifetime and color gamut. The pixel resolution in our study is 167ppi, which meets the requirement for automotive vehicle application. We discuss the film quality and picture quality from ink jet printing process to address which pixel arrangement design can meet the demand of products. Finally, a 12 inch AMOLED panel is realized in our study.